European and Japanese affiliates in India: differences in conduct and performance - Siddharthan, N.S. (1999)
This paper attempts to identify the variables that distinguish Japanese FDI from European FDI, and to test for their significance in differentiating the conduct and performance of Japanese and European firms in India. There have been studies which demonstrated that multinational enterprises as a group behave differently from non-affiliated local firms. This study highlights intra-MNE differences related to nationality of the MNC, nature of the Indian partner and industry-specific characteristics. - Reproduced
Keywords: Investments, European; Investments, Japanese; Foreign investment